Kuala Lumpur Stock Index Futures Market Efficiency: Long Memory Approach - Ahmad, Norzalina; Mohd Taib, Hasniza (American Scientific Publishers, 2017)
This research focuses on the market efficiency tests using Fractional Integration approach. This approach involves testing the long memory component in the futures basis, which leads to the rejection of the market efficiency if there is an existence of the long memory.Data used consist of the Kuala Lumpur Composite Index (KLCI) futures contract and spot prices of KLCI from year 2000 to 2015.Based on ARFIMA model, there is evidence of long memory component in the KLCI futures basis, which suggests that KLCI futures price is inefficient.This leads us to conclude that the KLCI futures price is biased in predicting future spot prices; and therefore past price might be used to predict future prices.